2012
DOI: 10.1111/j.1600-079x.2012.00995.x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Melatonin attenuates inflammation and promotes regeneration in rabbits with fulminant hepatitis of viral origin

Abstract: The objective of the present study was to investigate the effect of melatonin on the liver inflammatory and regenerative response in an animal model of fulminant hepatic failure (FHF) of viral origin. Rabbits were experimentally infected with 2×10(4) hemagglutination units of a rabbit hemorrhagic disease virus (RHDV) isolate and received melatonin at two concentrations of 10 or 20mg/kg at 0, 12 and 24hr postinfection. RHDV infection induced an inflammatory response, with increased expression of toll-like recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 59 publications
4
61
0
1
Order By: Relevance
“…Therefore, ER stress inhibition could be used as a possible therapeutic strategy to reduce apoptotic cell death in FHF. In an animal model of FHF of viral origin induced by infection with the rabbit hemorrhagic disease virus (RHDV) , melatonin inhibited apoptosis in a dose‐dependent manner and enhanced liver regeneration .…”
Section: Melatonin and Liver Diseasesmentioning
confidence: 99%
“…Therefore, ER stress inhibition could be used as a possible therapeutic strategy to reduce apoptotic cell death in FHF. In an animal model of FHF of viral origin induced by infection with the rabbit hemorrhagic disease virus (RHDV) , melatonin inhibited apoptosis in a dose‐dependent manner and enhanced liver regeneration .…”
Section: Melatonin and Liver Diseasesmentioning
confidence: 99%
“…Additionally, melatonin reduced phosphorylated Janus kinase expression and enhanced extracellular mitogen-activated protein kinase (ERK) and signal transducer and activator of transcription (STAT) 3 expression. It has been shown that melatonin had an anti-inflammation effect and stimulated regenerative mechanisms in rabbits infected by RHDV [138]. Concomitantly, hepatocyte apoptosis was crucial in the progress of fulminant hepatitis infected by RHDV.…”
Section: Protective Effects Of Melatonin On Hepatitismentioning
confidence: 99%
“…Silymarin (200mg/Kg/day) (Li et al 2012) cholorogenic acid (60 mg/Kg/day) ( Shi et Al. 2009) and melatonin (20 mg/Kg/day) (Laliena et al 2012) were suspended in gum acacia (2% w/v) and given orally once daily for 21 successive days, 24h post CCl 4 injection. After the experimental period, blood samples were collected from each animal in all groups into sterilized tubes for serum separation.…”
Section: Animals and Treatmentsmentioning
confidence: 99%